2020
DOI: 10.3390/foods9010040
|View full text |Cite
|
Sign up to set email alerts
|

Could Defatted Mealworm (Tenebrio molitor) and Mealworm Oil Be Used as Food Ingredients?

Abstract: Before edible insects may be used as an alternative food, it is necessary to develop basic product forms and evaluate their characteristics. We made two basic commercial products (defatted powder and oil) from mealworm, a popular edible insect. The defatted mealworm powder possessed a sufficient amount of protein, and it had a savory taste due to plentiful free amino acids. Additionally, it had abundant minor nutrients and bioactive compounds. The physicochemical properties of mealworm oil were very similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 37 publications
6
70
0
Order By: Relevance
“…Our results are also in accordance with reported data by Son et al regarding the predominant FFA within insects (myristic, palmitic and for oleic) [28]. Lou et al analyzed the frass of PS-fed larvae and also identified long chain FFAs, such as oleic acid (C 18 H 34 O 2 ), octadecanoic acid (C 18 H 36 O 2 ) and n-hexadecanoic acid (C 16 H 32 O 2 ), as well as the PS trimer (1,3,5,-triphenyl-cyclohexane), findings fully aligned with the results of this work [3].…”
Section: Analytical Methods and Identified Compoundssupporting
confidence: 94%
See 2 more Smart Citations
“…Our results are also in accordance with reported data by Son et al regarding the predominant FFA within insects (myristic, palmitic and for oleic) [28]. Lou et al analyzed the frass of PS-fed larvae and also identified long chain FFAs, such as oleic acid (C 18 H 34 O 2 ), octadecanoic acid (C 18 H 36 O 2 ) and n-hexadecanoic acid (C 16 H 32 O 2 ), as well as the PS trimer (1,3,5,-triphenyl-cyclohexane), findings fully aligned with the results of this work [3].…”
Section: Analytical Methods and Identified Compoundssupporting
confidence: 94%
“…The latter effect can be connected also to the degradation of styrene, styrene oligomers, acetophenone and cumyl alcohol. In their case, an initial increase from day 0 to day 3 led to a decrease at day 7, something that can be explained from enzymatic activity and conversion of the ingested chemicals into CO 2 , as it has been already reported [5,19,28].…”
Section: Release and Fate Of The Identified Chemical Compoundsmentioning
confidence: 58%
See 1 more Smart Citation
“…Yang-Ju Son and colleagues [ 37 ] used mealworms to produce a defatted powder and mealworm oil. While the powder was rich in protein, minerals, and bioactive compounds and had a pleasant taste, the mealworm oil contained bioactive nutrients, especially gamma tocopherol, and had physicochemical properties that were similar to those of vegetable oil.…”
Section: Resultsmentioning
confidence: 99%
“…A mealworm protein diet has been used to feed pets and zoo animals, including birds, reptiles, small mammals, batrachians, and fish (Veldkamp 2012). Commercial food products such as defatted powder and oil have been processed from mealworms that are sourced with bioactive nutrients such as α‐tocopherol, functional peptides, and glucosamine derivatives such as chitin and chitosan (Son et al 2020). Most importantly, mealworms are convenient experimental models to study host–pathogen/parasite interactions, innate immunity signaling cascades, and antimicrobial peptide (AMP) profiles in Coleopteran and other insects; the findings in mealworms can be extrapolated to other species among the invertebrates and vertebrates (De Souza et al 2015; Jo et al 2019; Jozefiak & Engberg 2017; Vigneron et al 2019).…”
Section: Introductionmentioning
confidence: 99%